2018
DOI: 10.1002/ps.4924
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal toxicities and synergistic activities of Salvia lavandulifolia oil constituents against synanthropic mites

Abstract: This study is the first report on the acaricidal activity of S. lavandulifolia oil and the synergistic interactive effects of its components against D. farinae, D. pteronyssinus and T. putrescentiae. The oil may be an alternative tool for the control of synanthropic mites. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Borneol, have been found to have antioxidant and antibacterial properties [75,76]. In addition, essential oils made from plants, such as Salvia lavandulifolia and Melissa officinali (France), could remove house dust mites from our living environment [74,75,[77][78][79][80][81][82][83][84][85][86][87][88]. In contrast, investigations of their inhibitory ability toward allergens are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Borneol, have been found to have antioxidant and antibacterial properties [75,76]. In addition, essential oils made from plants, such as Salvia lavandulifolia and Melissa officinali (France), could remove house dust mites from our living environment [74,75,[77][78][79][80][81][82][83][84][85][86][87][88]. In contrast, investigations of their inhibitory ability toward allergens are limited.…”
Section: Discussionmentioning
confidence: 99%
“…6 Flavonoids, monoterpenoids, and triterpenes were reported from the aerial parts of the plant. 1 S. lavandulifolia EO demonstrated moderate anti-inflammatory activity (IC 50 = 30 μg/mL) 1 ; moderate cytotoxicity against human leukemia (HL60), myelogenous leukemia (K562), breast (MCF7), and ovarian (A2780) cancer cell lines 7 ; antioxidant 4 ; in vitro acetylcholinesterase inhibitory activity 8 ; antiseptic, analgesic and sedative properties 9 ; weak antimalarial activity against Plasmodium falciparum 1 ; acaricidal toxicity against synanthropic mites 10 ; strong antifeedant effects against Leptinotarsa decemlineata , Spodoptera littoralis , Myzus persicae , and Rhopalosiphum padi 11 ; phytotoxic activity against Lactuca sativa and Lolium perenne 11 ; and antifungal activity against Fusarium sp. 11 and Candida albicans.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported acaricidal activity of many EOs such as garlic, basil, bergamot, black pepper, caraway seed, cedarwood, clove, citronella, eucalyptus, lavender, lemon, hot pepper, ginger and rosemary (Nechita et al 2015;Zandi-Sohani and Ramezani 2015;Tak and Isman 2017;Kim et al 2018;Lee et al 2018). Rosemary EO has been investigated for biological activities by several workers (Elamrani et al 2000;Tak and Isman 2016).…”
Section: Introductionmentioning
confidence: 99%